Physical and chemical properties of coconut coir dust and oil palm empty fruit bunch and the growth of hybrid heat tolerant cauliflower plant - Ahmad, Asiah; Ismail, Mohd Razi; Yusop, Mohd Khanif; Mahmood, Maziah; Mohd, Shaharuddin (Universiti Putra Malaysia Press, 2004)
This research report is about the physical and chemical properties of coconut coir dust (CD) and oil palm empty fruit bunch (EFB), and their potential for use as growing media for hybrid cauliflower grown under humid tropical greenhouse conditions. The physical properties showed that both the EFB and CD provided optimum plant growth conditions at the start of the growing the period. However, the readily available water value for CD was 34% whereas that for EFB was 19%. The air filled porosity containing more pores larger than 300 11m were higher in EFB compared to CD. The chemical properties data suggested that EFB was more alkaline (PH of 6.9) than CD (PH of 5.3) and had lower electrical conductivity (EC) of 1.3 dSm-1 than CD (l.9 dSm,l). The results also indicated higher nutrient contents in CD than in EFB. Despite a high initial EC value for CD than EFB, the hybrid cauliflower plant dry weights and total leaf area for CD grown plants were double those grown in EFB. The appearance offungus and mushroom on the EFB medium surface and the early sign of decomposition may account for the lower plant growth in the EFB medium. Hence, CD is a more suitable growing medium for growing hybrid cauliflower compared to EFB.